An Islamic Legal Perspective on the Practice of Areca Nut Trading on Credit (A Case Study in Dusun Selamat, Lagan Tengah Village) - Puji astuti, Fuji Lestari; kurniawan; Sunarti, Zeni; Fatimah, Siti; Dewi, Hasna (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: This study aims to examine the practice of areca nut trading on credit that takes place in Dusun Selamat, Lagan Tengah Village, Geragai Subdistrict, East Tanjung Jabung Regency, and to assess its conformity with Islamic law. Methodology: This research employs a qualitative method using a case study approach. Data were collected through interviews, observations, and documentation to explore the real-life practices of credit-based areca nut transactions between farmers and buyers (middlemen). Main Findings: The findings show that the credit-based areca nut trading practice in Dusun Selamat fulfills the essential pillars and requirements of sale and purchase in Islam. These include mutual consent (antaradin minkum), clarity regarding the object and price, and the absence of coercion or fraud. Moreover, this practice benefits both parties, particularly in supporting farmers' economic needs. Novelty/Originality of this study: This study provides a contextual analysis of a localized credit-based trade practice in rural Indonesia and offers an Islamic legal perspective that has not been widely documented in previous literature. It contributes original insights into how Islamic principles are applied in informal agricultural transactions and highlights the permissibility (mubah) of such practices when grounded in justice, transparency, and mutual satisfaction.